613 Fontan associated nephropathy: does diastolic function play a role?. (8th December 2021) - Rotella, Marta; Meneghesso, Davide; Sabatino, Jolanda; Biffanti, Roberta; Partigiani, Nicola Bertazza; Binda, Beatrice; Puricelli, Filippo; Chemello, Liliana; Cavalletto, Luisa; Padalino, Massimo; Salvo, Giovanni Di
Abstract: Aims: In Fontan patients, the pathophysiology of diastolic function and its relationship with systemic complications are still not well understood. Methods and results: This is a prospective study including patients who underwent Fontan completion in our centre between 1993 and 2016. We excluded patients with major congenital renal anomalies, those who underwent cardiac transplantation and redo -Fontan patients. All the subjects underwent clinical evaluation, laboratory exams with complete renal and hepatic function, transient hepatic elastography, and complete cardiac evaluation. We used Schwartz equation for estimating glomerular filtration rate in patients younger than 18 years, and CDK-EPI equation for adult patients. We enrolled 35 patients, 46% female ( N  = 16), and 54% male ( N  = 19). Medium age was 17 years old (range: 10–31 years old). Medium time from Fontan completion was 160 months (range: 57–340 months). Ten patients had a functional single left ventricle (FSLV, 28.5%) and 21 a functional single right ventricle (FSRV, 60%); four patients had an undetermined single ventricle (11.5%). Data from renal function assessment showed a prevalence of stage 2 chronic kidney disease (eGFR: 60–89 ml/min 1.73 mq). Of those, 11% with creatinine-based equation and 26% ( N  = 9) when using cystatin C-based equation, with one patients showing a moderate reduced loss of kidney function (eGFR: 40–59 ml/min/1.73 mq). Most of the patients with reduced eGFR measured with cystatin C were FSRV (89%). None had laboratory markers of acute tubular damage, but four patients had signs of chronic tubular dysfunction with elevation of beta 2 microglobulin (13%). Echocardiographic evaluation of diastolic function showed two patients with baseline E/A < 1 (6%, tot N  = 33) and 11/33 (33%) pts with abnormal E / E ′ (>12). All of them were FSRV patients (100%). Interestingly, statistical correlation between diastolic parameters and renal function showed a significant association between tubular damage parameters, such as alfa1microglobulin and beta2microglobulin, and E / E ′ (Pearson's R 0.4 and 0.48, respectively, P  < 0.05), both for FSLV and FSRV patients. Diastolic function appeared to be associated also with glomerular filtration: we found a statistically significant direct correlation between diastolic pulmonary wave deceleration time (dt D wave) and creatinine value (Pearson's R 0.49, P  < 0.05). Supporting the role of diastolic function in Fontan systemic complications is the linear correlation we found with hepatic tests: higher values of aspartate aminotransferase and of gamma-glutamyltransferase were associated with worse diastolic ventricular filling (longer dt D wave and E wave deceleration time, lower TDI early diastolic wave; Pearson's R 0.45, 0.5, and −0.41, respectively, P  < 0.05). Conclusions: Fontan-related nephropathy is associated with worsening diastolic function, which was more represented in FSRV patients. Diastolic function is also associated with liver disease in Fontan patients. Those data suggest renal and liver function should be closely monitored in patients with impaired diastolic function.